Put research on its way - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Knowing where you re going. Information systems for agricultural research management By R Vernon, ISNAR-CTA co-publication, 2001. 376 pp. ISBN 92 9118 054 8 CTA number 1075, 40 credit points.